Emily Writebol: capstone - Writebol, Emily, artist (Colorado State University. Libraries, 2019)
The artist's statement: I am a graphic designer and visual communicator. Strong design is essential in our increasingly visual world. I believe that no matter if it's a poster, business card, or, website how something is designed, determines how it is experienced. I am a communicator who uses photography, type, and illustrations to convey concepts and ideas. Whenever I approach a new design challenge, I utilize sketching, planning, experimenting, and research in order to find inspiration and make my design fulfill its purpose. My process leads me to my inspiration. It is not unusual for me to discover new concepts or ideas as I work through experimenting or my own intuition. I am constantly finding inspiration within playing or experimenting with the software, even if an approach does not pan out: it always teaches me something about the design. My work is divergent in essence and always converges depending on the project's goal.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design